Lithium titanium aluminum phosphate composite polymer as well as preparation method and application thereof

The silane coupling agent modified lithium titanium aluminum phosphate and polymer cross-linked polymerization to form a composite polymer, which solves the problem of poor stability of LATP to lithium and achieves high stability and long life of the electrolyte.

CN119890435AActive Publication Date: 2025-04-25DONGGUAN SHENGXINDA TRADING CO LTD

Patent Information

Application Number
CN202510369503.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

Lithium titanium aluminum phosphate (LATP) has poor stability to lithium, resulting in unstable electrolytes and short cycle life, limiting its application in lithium-ion batteries.

Method used

The titanium aluminum phosphate modified with silane coupling agent is cross-linked and polymerized with polymer monomer to form a titanium aluminum lithium phosphate composite polymer, and lithium ion conduction is improved through chemical bonding.

Benefits of technology

It improves the interface stability, electrochemical window width and room temperature ionic conductivity, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890435A_ABST
    Figure CN119890435A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium aluminum titanium phosphate composite polymer as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The preparation method of the titanium-aluminum-lithium phosphate composite polymer comprises the following steps: dissolving a polymer monomer and a lithium salt in an organic solvent in an inert atmosphere, then adding silane coupling agent modified titanium-aluminum-lithium phosphate, reacting, and then adding a cross-linking agent to carry out cross-linking polymerization on the polymer monomer and the silane coupling agent modified titanium-aluminum-lithium phosphate to obtain the titanium-aluminum-lithium phosphate composite polymer. And curing to obtain the lithium titanium aluminum phosphate composite polymer. Reaction sites dispersed in a polymer chain react with surface groups of the silane coupling agent modified LATP, so that the modified LATP particles are uniformly dispersed along the polymer chain. The LATP and the polymer are connected through a chemical bond, so that discontinuous conduction of lithium ions caused by an organic-inorganic interface of a traditional composite electrolyte is improved. The introduction of LATP makes the electrolyte have good mechanical properties and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a lithium aluminum titanium phosphate composite polymer and a preparation method and application thereof. Background Art

[0002] Lithium aluminum titanium phosphate (LATP) is one of the more mature NASICON ion fast conductors. It has good room temperature ion conductivity, low preparation cost, wide source of raw materials and good air stability. It is one of the most promising solid electrolytes for large-scale mass production. However, it has poor stability to lithium. During the charge and discharge cycle, Ti 4+ Will be restored to Ti 3+ , resulting in unstable electrolyte and short cycle life, which seriously limits its application in lithium-ion batteries.

[0003] The preparation of composite electrolytes by blending polymers with LATP helps to weaken the redox reaction on LATP during the charge and discharge process, thus helping to improve the life of the battery. However, traditional composite solid electrolytes are prepared by blending, and the inorganic nanoparticles and polymers are connected by physical interactions, which has poor reliability. In addition, there are organic-inorganic interface problems between polymers and inorganic nanoparticles, making it difficult for lithium ions to be continuously conducted along the polymer-inorganic nanoparticles. Not only that, considering the size effect of fillers in composite electrolytes, LATP powders usually require smaller particle sizes, but smaller particle sizes bring larger surface energy, which makes it easy for the powders to agglomerate during the mixing process. The poor dispersibility of LATP powders will lead to uneven interface potentials, which can easily lead to the growth of lithium dendrites. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a lithium titanium aluminum phosphate composite polymer and its preparation method and application. The room temperature conductivity of the lithium titanium aluminum phosphate composite polymer provided is 1.5×10 -5 ~6.6×10 -4 S cm -1 , the electrochemical stability window is 4.7~5.6V.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a lithium aluminum titanium phosphate composite polymer, comprising the following steps:

[0007] In an inert atmosphere, a polymer monomer and a lithium salt are dissolved in an organic solvent, and then lithium aluminum titanium phosphate modified by a silane coupling agent is added, and after the reaction, a cross-linking agent is added to cross-link and polymerize the polymer monomer and the lithium aluminum titanium phosphate modified by the silane coupling agent, and the lithium aluminum titanium phosphate composite polymer is obtained after curing;

[0008] The polymer monomer includes at least one of polyethylene glycol diacrylate (PEGDA) and polyethylene glycol diamine;

[0009] The silane coupling agent in the silane coupling agent-modified lithium titanium aluminum phosphate includes at least one of an amino silane coupling agent and a methacryloxy silane coupling agent;

[0010] The cross-linking agent includes at least one of ethylenediamine, polyetheramine and hexamethylenediamine.

[0011] Optionally, the inert atmosphere includes a nitrogen atmosphere or an argon atmosphere.

[0012] Preferably, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate and lithium bistrifluoromethanesulfonyl imide.

[0013] Preferably, the organic solvent comprises at least one of tetrahydrofuran, dichloromethane, chloroform, acetonitrile, toluene, dioxane and N,N-dimethylformamide.

[0014] Preferably, the amino silane coupling agent includes at least one of γ-aminopropyltriethoxysilane (KH550), γ-aminopropyltrimethoxysilane and γ-aminopropylmethyldiethoxysilane; the methacryloxysilane coupling agent includes γ-methacryloxypropyltrimethoxysilane (KH570) and / or γ-methacryloxypropyltri(trimethylsiloxy)silane.

[0015] The method of modifying lithium aluminum titanium phosphate with a silane coupling agent in the present invention can be a general method of modifying inorganic materials with a silane coupling agent.

[0016] Preferably, the polymer monomer and the lithium salt are added in a ratio of lithium oxygen EO:Li=8:1-16:1; and the addition amount of the silane coupling agent-modified lithium titanium aluminum phosphate is 5-40wt.% of the lithium titanium aluminum phosphate composite polymer.

[0017] Preferably, the reaction temperature is 25-80° C. and the reaction time is 0.5-6 h.

[0018] More preferably, when the polymer monomer is PEGDA and the silane coupling agent used for modification is modified to a methacryloxysilane coupling agent, an initiator is added, and the initiator includes azobisisobutyronitrile (AIBN).

[0019] The second technical solution of the present invention is to provide a lithium aluminum titanium phosphate composite polymer prepared according to the preparation method of the lithium aluminum titanium phosphate composite polymer.

[0020] The third technical solution of the present invention is to provide an application of the above-mentioned lithium aluminum titanium phosphate composite polymer in a solid electrolyte.

[0021] The fourth technical solution of the present invention is to provide an application of the above-mentioned lithium aluminum titanium phosphate composite polymer in a lithium ion battery.

[0022] The beneficial technical effects of the present invention are as follows:

[0023] The present invention utilizes the dispersed reaction sites in the polymer chain to react with the surface groups of the silane coupling agent modified LATP, so that the modified LATP particles are evenly dispersed along the polymer chain. LATP and the polymer are connected by chemical bonds, which improves the discontinuous conduction of lithium ions caused by the organic-inorganic interface of the traditional composite electrolyte. The introduction of LATP makes the electrolyte have good mechanical properties and thermal stability. The lithium aluminum titanium phosphate composite polymer has good interface stability, a wide electrochemical window (>4.5V) and high room temperature ionic conductivity (>10 -5 S cm -1 ).

[0024] The lithium aluminum titanium phosphate composite polymer of the invention has a simple preparation process and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the synthesis of lithium aluminum titanium phosphate composite polymer according to Example 1 of the present invention. DETAILED DESCRIPTION

[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0028] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] Example 1

[0031] Preparation of lithium aluminum titanium phosphate composite polymer:

[0032] (1) Premix anhydrous ethanol (15 mL) and LATP (1 g) to form a uniform white dispersion. Separately, mix silane coupling agent KH550 (1 mL) with anhydrous ethanol (10 mL), add deionized water (1 mL), and stir at room temperature for about 2 hours to hydrolyze the silane coupling agent. Then add the silane coupling agent solution to the LATP dispersion and stir at 60°C for 6 hours. Then centrifuge the dispersion and wash with anhydrous ethanol, repeat three times, and dry at 60°C in a vacuum to obtain a white powder, which is silane coupling agent modified LATP (KH550@LATP).

[0033] (2) In a glove box filled with argon, PEGDA 400 (1 mL), lithium bis(trifluoromethanesulfonyl)imide (312 mg) and acetonitrile (1 mL) were mixed until the lithium salt was completely dissolved (PEGDA 400 The lithium oxygen ratio of the mixture with lithium bis(trifluoromethanesulfonyl)imide was EO:Li=8:1). KH550@LATP powder (146 mg) was then added, ultrasonicated for 30 minutes to completely disperse it in the solution, and stirred at 60°C for 2 hours to allow the polymer monomer to fully react with the surface groups of the modified LATP. Then the heating was stopped and the crosslinking agent ethylenediamine (EDA, 80 μL) was added. After stirring evenly, it was poured into a polytetrafluoroethylene mold and heated at 60°C for 4 hours to completely cure it. It was then vacuum dried at 60°C to remove excess solvent. A white and smooth lithium aluminum titanium phosphate composite polymer (PEGDA-EDA-KH550@LATP) was obtained, in which the KH550@LATP powder accounted for 10wt.%.

[0034] The schematic diagram of synthesizing lithium aluminum titanium phosphate composite polymer in Example 1 of the present invention is shown in Figure 1 .

[0035] Example 2

[0036] Preparation of lithium aluminum titanium phosphate composite polymer:

[0037] The difference from Example 1 is that the crosslinking agent used is polyetheramine 400 (PPGBAE, 0.5 mL) was added to prepare lithium aluminum titanium phosphate composite polymer PEGDA-PPGBAE-KH550@LATP. Other implementation conditions were the same as those in Example 1.

[0038] Example 3

[0039] Preparation of lithium aluminum titanium phosphate composite polymer:

[0040] The difference from Example 1 is that the cross-linking agent used is hexamethylenediamine (HDA, 80 μL), and the lithium aluminum titanium phosphate composite polymer PEGDA-HDA-KH550@LATP is prepared. The other implementation conditions are the same as those in Example 1.

[0041] The performance of the lithium aluminum titanium phosphate composite polymer obtained in Examples 1-3 was characterized, and the test results are shown in Table 1.

[0042] Table 1 Properties of lithium aluminum titanium phosphate composite polymers obtained in Examples 1-3

[0043] Example Average thickness(mm) <![CDATA[Ionic conductivity (S·cm -1 , 25 °C)]]> Electrochemical stability window (V) 1 0.036 <![CDATA[0.662×10 -4 ]]> 5.04 2 0.033 <![CDATA[1.33×10 -4 ]]> 5.19 3 0.034 <![CDATA[0.878×10 -4 ]]> 5.14

[0044] As can be seen from Table 1, as the length of the diamine segment increases, the ionic conductivity increases. This may be because when the length of the diamine segment is short, the polymer cross-linking density is large, and the flexibility of the lithium aluminum titanium phosphate composite polymer decreases, resulting in a decrease in ionic conductivity. When there are a large number of ether oxygen structures in the diamine segment, the lithium conductivity of the polymer chain is enhanced, so the ionic conductivity increases.

[0045] Example 4

[0046] Preparation of lithium aluminum titanium phosphate composite polymer:

[0047] The difference from Example 1 is that the silane coupling agent used is KH570 (1 mL), and the modified LATP obtained is KH570@LATP. AIBN is used as an initiator to initiate the free radical polymerization of KH570@LATP and PEGDA to obtain a lithium aluminum titanium phosphate composite polymer PEGDA-EDA-KH570@LATP. The other implementation conditions are the same as those in Example 1.

[0048] Example 5

[0049] Preparation of lithium aluminum titanium phosphate composite polymer:

[0050] The difference from Example 4 is that the cross-linking agent used is hexamethylenediamine (HDA, 80 μL), and the lithium aluminum titanium phosphate composite polymer PEGDA-HDA-KH570@LATP is prepared. The other implementation conditions are the same as those of Example 4.

[0051] Example 6

[0052] Preparation of lithium aluminum titanium phosphate composite polymer:

[0053] The difference from Example 4 is that the crosslinking agent used is polyetheramine 400(PPGBAE, 0.5 mL) was added to prepare lithium aluminum titanium phosphate composite polymer PEGDA-PPGBAE-KH570@LATP. Other implementation conditions were the same as those in Example 4.

[0054] The performance of the lithium aluminum titanium phosphate composite polymer obtained in Examples 4-6 was characterized, and the test results are shown in Table 2.

[0055] Table 2 Properties of lithium aluminum titanium phosphate composite polymers obtained in Examples 4-6

[0056] Example Average thickness(mm) <![CDATA[Ionic conductivity (S·cm -1 , 25 °C)]]> Electrochemical stability window (V) 4 0.034 <![CDATA[1.232×10 -4 ]]> 5.09 5 0.034 <![CDATA[1.709×10 -4 ]]> 5.15 6 0.037 <![CDATA[5.332×10 -4 ]]> 5.19

[0057] It can be seen from Table 2 that when the LATP surface modified silane coupling agent is replaced with KH570, the performance of the composite electrolytes prepared by each cross-linking agent is improved. This is mainly because the surface of LATP modified by KH570 is an acrylate bond, which has better hydrophobicity and is more evenly dispersed in organic solvents, further weakening the agglomeration and improving the ionic conductivity.

[0058] Example 7

[0059] Preparation of lithium aluminum titanium phosphate composite polymer:

[0060] The difference from Example 1 is that the solvent used in step (2) is N,N-dimethylformamide (1 mL), and the other implementation conditions are the same as those in Example 1.

[0061] Example 8

[0062] Preparation of lithium aluminum titanium phosphate composite polymer:

[0063] The difference from Example 1 is that the solvent used in step (2) is dichloromethane (1 mL), and the other implementation conditions are the same as those in Example 1.

[0064] Example 9

[0065] Preparation of lithium aluminum titanium phosphate composite polymer:

[0066] The difference from Example 1 is that the solvent used in step (2) is tetrahydrofuran (1 mL), and the other implementation conditions are the same as those in Example 1.

[0067] The performance of the lithium aluminum titanium phosphate composite polymers obtained in Examples 7-9 was characterized, and the room temperature ionic conductivity was 5.34×10 -5 S cm -1 ,7.96×10 -5 S cm -1 , 6.30×10 -5 S cm -1; The electrochemical stable point windows are 5.03V, 5.18V and 5.12V respectively.

[0068] Example 10

[0069] Preparation of lithium aluminum titanium phosphate composite polymer:

[0070] The difference from Example 1 is that the lithium salt used in step (2) is lithium tetrafluoroborate (LiBF4), EO:Li=8:1, and the other implementation conditions are the same as those in Example 1.

[0071] Embodiment 11

[0072] Preparation of lithium aluminum titanium phosphate composite polymer:

[0073] The difference from Example 1 is that the lithium salt used in step (2) is lithium hexafluoroborate (LiBF6), EO:Li=8:1, and the other implementation conditions are the same as those in Example 1.

[0074] The performance of the lithium aluminum titanium phosphate composite polymer obtained in Examples 10-11 was characterized, and the room temperature ionic conductivity was 6.64×10 -5 S cm -1 ,7.13×10 -5 S cm -1 ; The electrochemical stable point windows are 5.15V and 5.21V respectively.

[0075] Example 12

[0076] Preparation of lithium aluminum titanium phosphate composite polymer:

[0077] The difference from Example 1 is that EO:Li=16:1, and the other implementation conditions are the same as those of Example 1.

[0078] Embodiment 13

[0079] Preparation of lithium aluminum titanium phosphate composite polymer:

[0080] The difference from Example 1 is that EO:Li=12:1, and the other implementation conditions are the same as those of Example 1.

[0081] The performance of the lithium aluminum titanium phosphate composite polymers obtained in Examples 12-13 was characterized, and the room temperature ionic conductivity was 2.24×10 -5 S cm -1 , 3.27×10 -5 S cm -1 The decrease in conductivity is due to the increase in EO:Li, which leads to an increase in crystallinity. At the same time, the decrease in Li ion concentration in the electrolyte also leads to a decrease in ionic conductivity.

[0082] Embodiment 14

[0083] Preparation of lithium aluminum titanium phosphate composite polymer:

[0084] The difference from Example 1 is that the addition amount of KH550@LATP is 5 wt.% of the lithium aluminum titanium phosphate composite polymer, and the other implementation conditions are the same as those of Example 1.

[0085] Embodiment 15

[0086] Preparation of lithium aluminum titanium phosphate composite polymer:

[0087] The difference from Example 1 is that the addition amount of KH550@LATP is 20 wt.% of the lithium aluminum titanium phosphate composite polymer, and the other implementation conditions are the same as those of Example 1.

[0088] Example 16

[0089] Preparation of lithium aluminum titanium phosphate composite polymer:

[0090] The difference from Example 1 is that the addition amount of KH550@LATP is 30 wt.% of the lithium aluminum titanium phosphate composite polymer, and the other implementation conditions are the same as those of Example 1.

[0091] Embodiment 17

[0092] Preparation of lithium aluminum titanium phosphate composite polymer:

[0093] The difference from Example 1 is that the addition amount of KH550@LATP is 40 wt.% of the lithium aluminum titanium phosphate composite polymer, and the other implementation conditions are the same as those of Example 1.

[0094] The performance of the lithium aluminum titanium phosphate composite polymers obtained in Examples 14-17 was characterized, and the room temperature ionic conductivity was 3.18×10 -5 S cm -1 , 6.22×10 -5 S cm -1 5.28×10 -5 S cm -1 , 3.98×10 -5 S cm -1 The change in conductivity first increases and then decreases with the concentration change. This is mainly because when the filler concentration is 5wt.%, the inorganic filler contributes less to the ionic conductivity and the improvement is small; as the concentration of inorganic particles increases, new lithium ion transmission channels are formed, and the ionic conductivity is improved; when it exceeds a certain threshold, due to a certain degree of agglomeration, the surface area decreases, which hinders the transmission of lithium ions, so the ionic conductivity tends to decrease.

[0095] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a lithium aluminum titanium phosphate composite polymer, characterized in that: The following steps are involved: In an inert atmosphere, a polymer monomer and a lithium salt are dissolved in an organic solvent, and then lithium aluminum titanium phosphate modified by a silane coupling agent is added, and after the reaction, a cross-linking agent is added to cross-link and polymerize the polymer monomer and the lithium aluminum titanium phosphate modified by the silane coupling agent, and the lithium aluminum titanium phosphate composite polymer is obtained after curing; The polymer monomer includes at least one of polyethylene glycol diacrylate and polyethylene glycol diamine; The silane coupling agent in the silane coupling agent-modified lithium titanium aluminum phosphate includes at least one of an amino silane coupling agent and a methacryloxy silane coupling agent; The cross-linking agent includes at least one of ethylenediamine, polyetheramine and hexamethylenediamine.

2. The method for preparing the lithium aluminum titanium phosphate composite polymer according to claim 1, characterized in that: The lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate and lithium bistrifluoromethanesulfonyl imide.

3. The method for preparing the lithium aluminum titanium phosphate composite polymer according to claim 1, characterized in that: The organic solvent includes at least one of tetrahydrofuran, dichloromethane, chloroform, acetonitrile, toluene, dioxane and N,N-dimethylformamide.

4. The method for preparing the lithium aluminum titanium phosphate composite polymer according to claim 1, characterized in that: The amino silane coupling agent includes at least one of γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane and γ-aminopropyl methyldiethoxysilane; the methacryloxy silane coupling agent includes γ-methacryloxypropyl trimethoxysilane and / or γ-methacryloxypropyl tris(trimethylsiloxy)silane.

5. The method for preparing the lithium aluminum titanium phosphate composite polymer according to claim 1, characterized in that: The polymer monomer and the lithium salt are added in a ratio of lithium oxygen EO:Li=8:1-16:1; the addition amount of the silane coupling agent modified lithium titanium aluminum phosphate is 5-40wt.% of the lithium titanium aluminum phosphate composite polymer.

6. The method for preparing the lithium aluminum titanium phosphate composite polymer according to claim 1, characterized in that: The reaction temperature is 25-80°C and the reaction time is 0.5-6h.

7. A lithium aluminum titanium phosphate composite polymer obtained according to the method for preparing a lithium aluminum titanium phosphate composite polymer according to any one of claims 1 to 6.

8. Use of the lithium aluminum titanium phosphate composite polymer according to claim 7 in a solid electrolyte.

9. Use of the lithium aluminum titanium phosphate composite polymer according to claim 7 in lithium ion batteries.

Citation Information

Patent Citations

  • Gel composite polymer electrolyte membrane, preparation method thereof and lithium ion battery

    CN109755644A

  • Solid electrolyte, secondary battery, preparation method of secondary battery and electric device

    CN118589023A

  • Preparation method and low-temperature application of asymmetric double-layer wide-temperature-range non-flammable composite solid electrolyte

    CN118888834A

  • Development of a Supercapacitive Battery via In-situ Lithiation

    US20220131179A1

Cited By

  • Solid electrolyte membrane containing coaxial composite material as well as preparation method and application of solid electrolyte membrane

    CN121726495A